Identification of a modori-inducing proteinase in the threadfin bream: Molecular cloning, tissue distribution and proteinase leakage from viscera during ice storage. (15th November 2020) - Liu, Jin-Yang; Yoshida, Asami; Gao, Yi-Li; Shirota, Kazuya; Shiina, Yasuhiko; Osatomi, Kiyoshi
Highlights: The modori -inducing proteinase (SSP) was identified as a trypsin by cDNA cloning. SSP was synthesized and existed in digestive system under physiological conditions. SSP leaked from the viscera into the belly muscle of the fish during ice storage. The leakage of SSP into the belly muscle of the fish induced the modori phenomenon. Abstract: Previously we purified and characterized a sarcoplasmic serine proteinase (SSP) from the belly muscle of the threadfin bream as a modori -inducing proteinase. In our attempt to clarify the structure and physiological functions of SSP, we successfully cloned the full-length cDNA of SSP (ORF 726 bp). The deduced amino acid sequence of SSP (241 residues) was highly homologous to fish trypsinogen. The distribution of SSP mRNA and the proteinase activity in the tissue indicated that SSP was mainly synthesized and existed in the digestive system under physiological conditions. After ice storage of the threadfin bream without gutting, a high SSP activity was detected only in the belly muscle because of SSP leaked from the viscera. Therefore, it is desirable to use edible proteinase inhibitor to inactivate the leaked SSP during production of surimi -based products or to take effective measures to prevent the proteinase leakage during post-harvest storage.